2008
DOI: 10.1063/1.2975335
|View full text |Cite|
|
Sign up to set email alerts
|

Microstructuration induced differences in the thermo-optical and luminescence properties of Nd:YAG fine grain ceramics and crystals

Abstract: Third-order nonlinear optical response and photoluminescence characterization of tellurite glasses with different alkali metal oxides as network modifiers J. Appl. Phys. 110, 083110 (2011) In-plane thermal conductivity determination through thermoreflectance analysis and measurements J. Appl. Phys. 110, 084313 (2011) Tuning of a cavity in a silicon photonic crystal by thermal expansion of an elastomeric infill Appl. Phys. Lett. 99, 111113 (2011) Assessing the thermal conductivity of non-uniform thin-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
3
14
0
Order By: Relevance
“…Second, other studies suggest that impurity/grain boundary phonon scattering processes dominate at temperatures below the Debye temperature ( e . g ., T = 300 K), and thus, non‐uniformities of grain boundaries may be the primary reasons for the decrease in κ at room temperature for 1Ce:YAG 87,88,90 . Our results appear to support the latter hypothesis, although rare‐earth driven acoustic scattering cannot be ruled out.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Second, other studies suggest that impurity/grain boundary phonon scattering processes dominate at temperatures below the Debye temperature ( e . g ., T = 300 K), and thus, non‐uniformities of grain boundaries may be the primary reasons for the decrease in κ at room temperature for 1Ce:YAG 87,88,90 . Our results appear to support the latter hypothesis, although rare‐earth driven acoustic scattering cannot be ruled out.…”
Section: Discussionsupporting
confidence: 57%
“…% Ce). This has been previously described, 75,87,89,90 and there are two primary hypotheses for this phenomenon. First, the garnet structure possesses several optical-phonon modes which do not contribute to heat transport; thus, the majority of heat dissipation is dictated by acoustic phonons with wave numbers of <125 cm −1 .…”
Section: Thermophysical Properties Of Ce:yag Derived From Rus Analysismentioning
confidence: 74%
“…No such effects were observed for the fine-grained ceramics. [58,59] However, there are several major points of concern in this interpretation: first, these observed satellites are much more shifted from the main line N than the satellites M 1 reported previously in the global absorption spectra of crystals and ceramics. Second, as shown by the studies on crystals and ceramics, no luminescence can be observed for the M 1 pairs, even at low temperatures or at very high Nd concentrations (9 at.%).…”
Section: Discussionmentioning
confidence: 65%
“…[20][21][22][23]59] Fourth, large regions of enhanced C Nd would increase the global concentration of Nd pairs and modify the M satellite structure of the spectra; however, no obvious departure from the predictions of random distribution was observed in the global absorption spectra of these materials, up to high (9 at.% Nd concentrations. Fifth, no obvious lowering of performances of the lasers based on these ceramics compared with those having single crystals and which could be attributed to such large-scale Nd agglomerates was observed.…”
mentioning
confidence: 91%
“…[ 17 ] Active‐tip based, near‐field optics are realized by coating a standard tip with Ce 3+ ‐doped YAG particles. [ 234 ] YAG:Ce 3+ nanoparticles attached to biomolecules work as luminescent markers for bioimaging. [ 235,236 ] Ce 3+ –Yb 3+ ‐codoped YAG has been considered as a downconversion phosphor for modifying the solar spectrum.…”
Section: Aluminate Phosphors For Applicationsmentioning
confidence: 99%